1987
DOI: 10.1177/106002808702100516
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Ulcer-Recurrence Risk Factors Associated with Long-Term Cimetidine Prescribing

Abstract: The appropriateness of long-term cimetidine prescribing was evaluated retrospectively in 243 outpatients. Criteria defining appropriate indications for the use of cimetidine for longer than eight weeks were established. Of the 243 patients surveyed, 115 (47 percent) were considered to be inappropriately receiving long-term cimetidine, either because they had never been objectively studied radiographically or endoscopically (23 percent) or had negative results before initiation of therapy (24 percent). Risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies have found H2RAs prescribed and administered for an inappropriate length of time, 3 , 4 in inappropriate doses, 3 , 5 for inappropriate diagnoses, 3 , 6 and in the absence of clinically established need 4 , 8–10 . A recent study has reported all of these problems in a small group of Massachusetts nursing home residents 11 …”
mentioning
confidence: 97%
“…Previous studies have found H2RAs prescribed and administered for an inappropriate length of time, 3 , 4 in inappropriate doses, 3 , 5 for inappropriate diagnoses, 3 , 6 and in the absence of clinically established need 4 , 8–10 . A recent study has reported all of these problems in a small group of Massachusetts nursing home residents 11 …”
mentioning
confidence: 97%